ANALISIS DAMPAK PENYALURAN PEMBIAYAAN KREDIT USAHA RAKYAT (KUR) PADA PENDAPATAN UMKM (STUDI KASUS: NASABAH BSI KCP BUKITTINGGI PASAR AUR) - Katerine Salsabila; Novera Martilova (BORJUIS: JURNAL OF ECONOMY, 2024)
This research is motivated by indications that the development of MSMEs is slow due to limited capital, public understanding of accessing financing, and the difficulty of obtaining funds from financial institutions. The aim of the research is to identify the role of KUR financing from BSI in supporting micro, small and medium enterprises and to evaluate the impact of KUR distribution on MSME income. The research method used is field research with a descriptive qualitative approach. Primary and secondary data were collected through interviews and observations of BSI customers who received KUR at KCP Pasar Aur. Data analysis was carried out by data reduction, data presentation, and drawing conclusions. The research results show that Bank Syariah Indonesia provides KUR financing by providing capital assistance, input, recommendations and supervision in accordance with the principles of Islamic law. The impact of KUR distribution on MSMEs is positive, including increasing the number of business branches, adding employees, and expanding business equipment which contributes to increasing MSME income.